Economic integration in Africa : the East African Community in comparative perspective - Mshomba, Richard Elias, 1954- (Cambridge, United Kingdom; Cambridge University Press, 2019)
"In this work Richard E. Mshomba offers an in-depth analysis of economic integration in Africa with a focus on the East African Community (EAC), arguably the most ambitious of all the regional economic blocs currently in existence in Africa. Economic Integration in Africa provides more than just an overview of regional economic blocs in Africa. It also offers a rich historical discussion on the birth and death of the first EAC, starting with the onset of colonialism in the 1890s, and a systematic analysis of the birth, growth, and aspirations of the current EAC. Those aspirations include forming a monetary union and eventually an East African political federation. This book also examines the African Union's aspirations for continent-wide integration as envisioned by the Abuja Treaty. Mshomba carefully argues that maturity of democracy and good governance in each country are prerequisites for the formation of a viable and sustainable East African federation and genuine continentwide integration."--Publisher's summary.
Introduction -- Regional economic integration in Africa -- The colonial background of the former East African Community -- The rise and fall of the former East African Community -- The birth and growth of the current East African Community : the customs union -- The common market -- The road to a monetary union -- Aspirations for an East African political federation -- Aspirations for continent-wide integration -- Conclusion.
Includes bibliographical references (pages 213-230) and index.
Keywords: East African Community -- History; East African Community; x; Federal government -- Africa, Eastern; Federal government; International economic integration; Africa; East African Community; Economic integration; History; z; Africa, Eastern -- Economic integration -- History; Africa, East -- Economic integration -- History; Africa -- Economic integration; Africa; Africa, East; Eastern Africa; Afrique orientale -- x; Afrique -- 2; History